Students’ Perception Towards the Teacher’s Billingual Language Use in an EFL Classroom - Satriah, Siti; Agustina, Tiara; Kareviati, Evie (PROJECT (Professional Journal of English Education), 2019)
This research aims to analyze about the students’ perception towards the teacher’s bilingual language use in an EFL classroom and to find out the benefit of it. The participants of this research were 32 students of eleventh grade in social 1 at MA Negeri Cimahi. This research employed qualitative research as research methodology and the descriptive research as research design to analyze the data. The instruments that used in this research were questionnaire and interview. Based on the result of questionnaire, the researchers found that students gave positive response of 45,3% by answering “agree” and it proved that students perceived positively towards the bilingual language that is used by the teacher in the EFL classroom. While the result of interview revealed that basically students thought that the teacher’s bilingual language use can help them in learning English and make them easy to understand the material. So, it can be concluded that students perceived positively towards the languages that the teacher use in EFL classroom. The result of this research is expected teachers can be better in using the language instruction in the EFL classroom, which is it will be useful and makes students easier in the learning English process.